GEOMAGNETIC STUDIES AT KYIV UNIVERSITY: HISTORY AND PROSPECTS - Menshov, O.; Sukhorada, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper gives a brief historical overview of the geomagnetic studies at Kyiv University progressing from the first steps to the current stage. Early geomagnetic studies go back to the late 19th – early 20th century and are associated with the works by N.A. Umov and P.T. Pasalskiy. The school of geomagnetism formed at the Department of Geophysics in the forties of the 20th century and has since passed through several stages gradually branching into narrower fields of research: earth magnetic field, magnetic field anomalies, high resolution magnetometry. Another research area concerned with various magnetic properties included rock magnetism, environmental magnetism, soil magnetism, and atmospheric pollution magnetism to finally form a new branch of geophysics – agrogeophysics. Taras Shevchenko National University of Kyiv has provided a geomagnetic research site for the younger generation of geophysicists. The Student Research and Design Society (SRDS) founded by A. V. Sukhorada, Associate Professor, is a joint research team comprising the older generation supervisors (SRDS ex-members, including professors and researchers), postgraduate students (those who have gained appropriate scientific expertise), undergraduate students (promising young researchers – the succeeding generation for the scientific tradition to be passed on to), and the younger generation (high school students and members of the Junior Academy of Sciences). The SRDS facilities aid geology students in conducting laboratory analyses and experiments: measurements of magnetic and other physical properties of rock samples, soils, atmospheric air samples, treating and testing samples, microscopic study of magnetic mineralogy, etc. The Department of Geophysics, Taras Shevchenko National University of Kyiv, currently headed by Professor S. A. Vyzhva associates its recent achievements and future prospects for advancing the theory of geomagnetism with its close cooperation with international organizations such as IAGA, EAGE, EGU, and SEG.
Keywords: geomagnetism; Taras Shevchenko National University of Kyiv; geophysics